Pengaruh Perputaran Aktiva Tetap Dan Perputaran Piutang Terhadap Profitabilitas Pada Perusahaan Manufaktur Di BEI - Marentina Nofatilofa; Dian Efriyenti (Prosiding, 2022)
Companies that are able to face competition in the industrial world prioritize growth. This study aims to determine the effect of fixed asset turnover and receivables turnover on the return on assets of food and beverage companies listed on the Indonesia Stock Exchange during the 2016-2020 period, either partially or simultaneously. The population in this study are food and beverage companies listed on the Indonesia Stock Exchange from 2016 to 2020. The research sample consisted of 9 food and beverage companies obtained using a purposive sampling method. The type of research used in this research is descriptive quantitative. The data collection technique used is documentation. The technique of multiple linear regression analysis in analyzing the data used SPSS version 25 software. From the results of the analysis it can be concluded partially that the fixed asset turnover variable has no significant effect on return on assets, while accounts receivable turnover has a significant effect on return on assets. Simultaneously, fixed asset turnover and accounts receivable turnover have a significant effect. With a contribution value of 7.1% and the rest is influenced by other factors.